Structural change in feedlot cattle death loss rates - Buda, Mark; Raper, Kellie Curry; Riley, John Michael; Peel, Derrell S. (Frontiers in Veterinary Science, 2023)
Industry reports and anecdotal evidence indicate that the death loss rate in cattle feedlots has increased over time. Such increases in death loss rates impact feedlot cost and thus profitability. This study uses data from the Kansas Feedlot Performance and Feed Cost Summary from 1992 through 2017 to model feedlot death loss rate as a function of feeder cattle placement weight, days on feed, time, and seasonality in the form of monthly dummy variables. Three commonly used tests of structural change, including the CUSUM, CUSUMSQ, and Bai and Perron methods, are then used to examine the existence and nature of any structural changes in the proposed model. All tests indicate the presence of structural breaks in the model, including both systematic change and abrupt change. Following a synthesis of structural test results, the final model is modified to include a structural shift parameter for the period from December 2000 to September 2010. The initial and modified models both indicate that days on feed has a significant positive influence on death loss rate. Likewise, the trend variable in both indicates that death loss rates have increased systematically over the period studied. However, the structural shift parameter in the modified model is positive and significant for December 2000 to September 2010, indicating that death loss is higher on average during this period. Parallels between evidence of structural change and possible industry and environmental catalysts are also discussed.